On commutative nilalgebras of low dimension - Gutierrez Fernandez, J.C. (Algebra and Discrete Mathematics, 2010)
We prove that every commutative non-associative nilalgebra of dimension ≤7, over a field of characteristic zero or sufficiently large is solvable.